A highly reversible Li–O2 battery utilizing a mixed electrolyte and a cathode incorporating Co3O4. Issue 101 (30th September 2015) - Zeng, J.; Francia, C.; Amici, J.; Bodoardo, S.; Penazzi, N.
Abstract : Li–O2 cell using a EMITFSI–DMSO electrolyte exhibited a low voltage gap and a long cycle life maintaining a satisfactory discharge capacity. Abstract : The present work mainly focuses on aprotic electrolytes in order to improve the performance of Li–O2 cells. The single-solvent electrolytes are based on tetraethylene glycol dimethyl ether (TEGDME), dimethyl sulfoxide (DMSO) and ionic liquid 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide (EMITFSI), respectively. Compared to TEGDME and EMITFSI electrolytes, the DMSO electrolyte leads to higher reversible Li–O2 cells, even though decomposition of DMSO is observed. In this work, novel blended TEGDME (20 wt%)–DMSO (80 wt%), EMITFSI (20 wt%)–TEGDME (80 wt%) and EMITFSI (20 wt%)–DMSO (80 wt%) based electrolytes are first proposed and investigated in the assembled Li–O2 cells. Incorporating with a Co3 O4 catalysed cathode, the EMITFSI–DMSO electrolyte results in an optimized Li–O2 battery, showing a lower voltage gap and a higher reversibility. In such a system, 80% of the recharge occurs at a potential underneath 4.0 V vs. Li + /Li. The low recharge voltage can suppress the decomposition of DMSO and favour a longer cycle life. More than 65 consecutive cycles are achieved at a current density of 0.1 mA cm −2 with a cut-off capacity of 835 mA h gelectrode −1 . The improved electrochemical performance is attributed to the enhanced ionic conductivity of the mixed electrolyte. In addition, the EMITFSI–DMSO electrolyte is considered more stable, since the ionic liquid could alleviate the decomposition of DMSO provoked by the intermediate superoxides.